Penerapan Metode Newton Raphson Untuk Pendugaan Parameter Regresi Non Linear Cobb-Douglas - Karomah, Binti (JURNAL JENDELA MATEMATIKA, 2024)
Inference in Cobb-Douglas model problems is a form of statistical inference that helps solve inference problems that involve a combination of several distributions. One form of distribution is a parametric distribution, and the other is a nonparametric distribution. To model the nonlinear Cobb-Douglas distribution and perform inference, such as determining test statistics, you can use maximum likelihood and then continue using the Newton rapshon method. Parameter estimates for the Cobb-Douglas nonlinear regression model were determined using the maximum likelihood method which was assumed to be normally distributed. then analyze the estimator first to obtain the Cobb-Douglas regression model estimator using the second order Taylor series approach to obtain the Newton Rapshon method. Based on the research results, it was found that the general form of parameter estimation for the Cobb-Douglas nonlinear regression model using the Newton-Raphson iterative method is:-So the parameter estimator is in scalar form.